Analyzing Workforce Inclusion of the Deaf Population in Santa Marta - Mendivil Barceló, Eder Iván; Chinchilla Rincón, Gustavo Alberto; Portillo Mendinueta, Nayades (Ingeniería Solidaria, 2014)
This article is the product of a research study titled “Tools provided by systems engineering for workforce participation of deaf and/or mute people in the urban zone of the Santa Marta municipality”. This research looked for and analyzed technological tools that could help improve deaf and/or mute people’s performance to give them greater opportunities of finding employment. The study was conducted from May to October in 2011, using a quantitative descriptive cross-sectional design. This article presents the results of the analysis related to the workplaces of hearing-impaired people in Santa Marta, an analysis of the aptitude levels of the population studied, and some recommendations for improving their workforce participation. The article also presents software programs which can help them perform their jobs.